Fungicides Showcases of Integrated Plant Disease Management from Around the World - Nita, Mizuho (IntechOpen, 2013)
This book comprised of three sections that focus various aspects of fungicide usages and its consequences. In the eight-chapter first section, authors discuss implementation of Integrated Plant Disease Management on a wide array of crops grown in different parts of the world: wheat productions in Argentina and in the US; corn, cotton and Eucalyptus productions in Brazil; rice productions in India; peanut productions in the southern US; and pine seedling nurseries in Serbia. The second section is composed of two chapters that explore the possibility of natural products as fungicides. The final section discusses two interesting and important topics on the fungicide-fungus interaction that can influence the implementation of plant disease management practices, fungicide resistance and hormesis.